An update on cell surface proteins containing extensin-motifs - Borassi, Cecilia (2015)
In recent years it has become clear that there are several molecular links that interconnect the plant cell surface continuum, which is highly important in many biological processes such as plant growth, development, and interaction with the environment. The plant cell surface continuum can be defined as the space that contains and interlinks the cell wall, plasma membrane and cytoskeleton compartments. In this review, we provide an updated view of cell surface proteins that include modular domains with an extensin (EXT)-motif followed by a cytoplasmic kinase-like domain, known as PERKs (for proline-rich extensin-like receptor kinases); with an EXT-motif and an actin binding domain, known as formins; and with extracellular hybrid-EXTs. We focus our attention on the EXT-motifs with the short sequence Ser-Pro(3-5), which is found in several different protein contexts within the same extracellular space, highlighting a putative conserved structural and functional role. A closer understanding of the dynamic regulation of plant cell surface continuum and its relationship with the downstream signalling cascade is a crucial forthcoming challenge.